PENERAPAN FUZZY DALAM MENENTUKAN DAMPAK PENGGUNA SMARTPHONE DI KALANGAN MASYARAKAT - Winda Permata Sari; Winda Lidyasari; Muhammad Fachrur Rozi; Yulia Andini; Agus Perdana Windarto (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
This study aims to determine the impact of smartphone users among the community. Smartphones also have the ability in each of its features that can help or meet the needs of its users. Smartphones have become a part of everyone's lifestyle, ranging from children, adolescents, and adults. Many people do not realize that using a smartphone has an impact on users both internally and externally. In determining the impact of smartphone users among the public, there needs to be a support system, a support system used is the Fuzzy Tsukamoto method, in the Fuzzy Tsukamoto method the writer uses 4 variables namely distance, user, time and impact to determine the impact of smartphone users.Keywords : Smartphone, Fuzzy